2016
DOI: 10.18632/oncotarget.12847
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of MCP-1 and CCR2 genes and IgA nephropathy risk

Abstract: Monocyte chemoattractant protein-1 (MCP-1) and its receptor CCR2 stimulate inflammation response by activating and recruiting monocytes/macrophages. MCP-1 and CCR2 polymorphisms were reported to be associated with various diseases. To explore the relationship between MCP-1 and CCR2 polymorphisms and IgA nephropathy (IgAN), we conducted this case-control study by enrolling 351 IgAN patients and 310 health controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate potential associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The study included 351 patients with IgAN (229 males and 122 females, mean age of 32 ± 11.9 years) and 310 age- and sex-matched healthy controls (186 males and 124 females, mean age of 35 ± 12.6 years), details as shown in our previous studies [19-21]. There were no statistically significant differences between the two groups in terms of age and sex ( P ﹥0.05).…”
Section: Resultsmentioning
confidence: 94%
“…The study included 351 patients with IgAN (229 males and 122 females, mean age of 32 ± 11.9 years) and 310 age- and sex-matched healthy controls (186 males and 124 females, mean age of 35 ± 12.6 years), details as shown in our previous studies [19-21]. There were no statistically significant differences between the two groups in terms of age and sex ( P ﹥0.05).…”
Section: Resultsmentioning
confidence: 94%
“…The infiltration of these cells plays an important role in the progression of both anti-Thy1 nephritis 4,15,] and immunoglobulin A (IgA) nephritis. 16,17 On the basis of the glomerular gene expression profiles, immune cell infiltration initially triggers inflammation on day 1, which plays a crucial role in the development of anti-Thy1 nephritis. The inhibition of immune cell infiltration alleviated MC proliferation and ECM accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…13 CCL2 drives mononuclear macrophage infiltration. 16,[23][24][25] However, upstream regulators (particularly transcription factors) of the CCL2 pathway remain unknown. In the present study, DBP was an upstream regulator of CCL2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, genetic factors play an import role in the development and progression of IgAN [10]. Our previous studies also found that Megsin [11], MCP-1/CCR2 [12] and TLR1 [13] gene polymorphisms were associated with IgAN susceptibility in a Chinese Han population. However, the rs699 variant in AGT gene and rs5186 polymorphism in ATR1 genes did not confer the risk with IgAN [14].…”
Section: Introductionmentioning
confidence: 98%